Maps of Health Needs and their use for policy making - Olminski, J; Koziol, M; Bartolik, K (European journal of public health, 2020)
As the economies transform into data-centered, so does the healthcare system. Responding effectively to the current problems by making right decisions and setting up the adjusted policies, either on national or regional level, requires the evidence-based tool. The one developed in Poland is called 'Maps of Health Needs', which states an unbiased source of information to a broad spectrum of stakeholders. The project is the answer to the need of evidence based policy making. The process is based on four steps: firstly, the data on demographics, epidemiology, staff, provided services, infrastructure, etc., are gathered,after that, they are analyzed, using the combination of two fields of expertise: advanced programming and statistics with medical knowledge; the qualitative and quantitative indicators are settled, along with its forecast,subsequently, the conclusions for the system are drawn,finally, the recommendations on actions are set up. First maps were published on 2015. The project is a subject to the constant adjustments, as the maps are upgraded and updated yearly, according to the stakeholders' expectations. Lately the maps for the five most burdening problems have been published in a form of an online app, accompanied by an executive summary. The spectrum of use of the maps is broad, not only for health priorities and health policy. Project's results are also used to review the legitimacy of financing health investments from public funds. Moreover, the planning and monitoring of the system is enhanced. Recent examples include also geographical distribution of linear accelerators and locations for psychiatric centers.